Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The Level of Human Resource Talent Management in Jordanian Private Universities in the Digital AgeFatima AbdAlKaerrm Wahba, Ibrahim Ahmad Abujame, Sana Yaqoub banat 2. Evaluate the quality of services provided by The Ministry of Education and schools and their implications for the educational process in government schools operating in evening system for Syrians in Jordan from the teachers’ point of viewIman Hasan Mahmoud Al-Nsoor, Amany Hasan Mahmoud Al-Nsour, Rasha Mohammad Ali Al-Rahahleh 3. The degree of employment of distance education among secondary teachers from the point of view of school principals in Palestine in light of the Corona pandemicAseel Fuad Droubi, Ashraf Munther Al-Sayegh 4. The level of use of educational applications by teachers of students with intellectual disabilities to support their academic achievementAbdulaziz Musaed Alahmari, Turki Abdullah Al-Qarini 5. Annoying Calls Behavior among Sample of Students from Al-Quds UniversityJuma Barakat Abu fakheda 6. The relationship between inventive thinking and intelligence among talented middle school students in Makkah Al-MukarramahSara Awed Al-Osimi 7. Designing a proposed e-counseling program based on Web 2.0 applications to Reducing family stress of Parents of children with intellectual disabilitiesShrog Aidh Alswat, Ali Mohammad Alkalthamy Ashhry
Keywords: Journal of Educational and Psychological Sciences